Studying the effect of using plasma in the cleaning of archaeological glass : applied onselected artifacts - Nada Hamed Ali Ibrahim Jammaz; Mohamed Mohamed Moustafa Ibrahim; Nasser El Din Nabawi Morgan; Rania Abdel Gwad Noman Eloriby (2025)
The thesis studied a new point on how to use modern technologies (Plasma electrolysis technique) in cleaning several types of archaeological glass. Chapter 1 includes everything related to archaeological glass. Chapter2 includes everything related to plasma.Chapter 3 includes experimentalstudy, where it dealt with an experimental study on the use of plasma electrolysis technology in cleaning glass, and through this chapter the optimum conditions for cleaning glass were determined. In chapter 4, optimum conditions were applied in cleaning archaeological glass. The plasma has succeeded in cleaning the archaeological glass from various deterioration aspects.
(3JfGhdJ gPg GdQSGdI fbWI LOjOI Mhd cjajI GSJNOGe GdJbfjGJ GdMOjKI (B((3JbfjI GdJMdjd GdcgQHj ddHdGReG(B) (3aj JfXja YOI CfhGY ef GdRLGL GdCKQj(B. (3MjK JfGhd GdaUd GdChd cd eG jNU GdRLGL GdGKQj JfGhd GdaUd GdKGfj cd eG jNU GdHdGReG(B. (3GdaUd GdKGdK gh GdOQGSI GdJLQjHjI MjK JfGhd OQGSI JLQjHjI Mhd GSJNOGe Jbfjg HdGReG GdJMdjd GdcgQHj aj JfXja GdRLGL hef NdGd gPG GdaUd Je JMOjO GdXQha GdeKGdjI dJfXja GdRLGL(B. (3aj GdaUd GdQGHY Je JWHjb GdXQha GdeKGdjI aj JfXja bWY RLGLjI GKQjI(B. (3hbO fLMJ GdHdGReG aj JfXja GdRLGL GdGKQj ef eNJda GdGJSGNGJ(B. s
Thesis (M.Sc)-Cairo University, 2025.
Bibliography: pages 93-108.
Issues also as CD.
Text in English and abstract in Arabic & English.
Keywords: Conservation and restoration; (3GdMaX hGdJQejes; Glass -- Deterioration -- Conservation -- Cleaning -- Plasma -- Plasma electrolysis -- Islamic glass lamps -- Soot -- Gypsum